Feedstuff Considerations for Feeding Bulls - Matt Hersom; Todd Thrift (EDIS)
AN210, a 3-page fact sheet by Matt Hersom and Todd Thrift, assists beef cattle producers in feedstuff selection, addressing the whole cottonseed and gossypol issue, and organic vs. inorganic mineral program. Includes references. Published by the UF Department of Animal Sciences, January 2009.